The Hand of Nature in the Glove of Phenomenology: Reply to Gallagher. Issue 2 (3rd April 2018) - Rudder Baker, Lynne
Abstract: This article outlines several important agreements between Lynne Rudder Baker's philosophical program and Shaun Gallagher's target article, while also highlighting important differences. Like Gallagher, Baker does not believe that nature can be adequately understood from a reductive point of view. Unlike Gallagher, however, she argues against rethinking nature (or science) as a non-reductionist project, which instead focuses on 'holistic relations (brain-body-environment)' and not just on brains, for example. Regardless of whether the classic conception of nature is mainly a philosophical or a scientific construction, Baker argues we should leave the definition of science to the scientists. We can then begin with the classic conception of nature and show what in nature cannot be explained by science so conceived. The robust first-person perspective, she claims, is precisely one such feature of nature: a dispositional property that no naturalist can accept as ontologically significant. So, while Baker agrees with Gallagher that the classic conception of nature (and science) is reductionistic, she does not accept that the sciences—whether reductionistic or not—can explain everything in nature. If that is right, then scientific naturalism, which does accept this claim, is straightforwardly false.